2018
DOI: 10.23736/s1973-9087.17.04533-6
|View full text |Cite
|
Sign up to set email alerts
|

Can vitamin D deficiency influence muscle performance in postmenopausal women? A multicenter retrospective study

Abstract: This study reported the frequency of hypovitaminosis D in postmenopausal women and its influence on the reduction of muscle mass, strength, and physical performance in a typical population referring to the physiatrist for musculoskeletal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…In another study, vitamin D was positively associated with isometric flexion and extension average torque at the knee and isokinetic flexion strength at 60°·s −1 and 180°·s −1 ; there was no correlation between vitamin D and knee isokinetic extension strength at 60°·s -1 and 180°·s −1 (12). Previous studies have suggested that vitamin D affected isometric muscle strength (7)(8)(9)(10)(11) and isokinetic muscle strength (7,12,13), but other reports have proposed no effect (12,(14)(15)(16)(17). In this study, improvement was observed in the knee flexor as well as extensor torque and power at 60°·s −1 and 180°·s −1 in all assessed age groups, and the between-group effect sizes for flexion power at 60°·s −1 and extension power at 180°·s −1 after vitamin D supplementation suggested that vitamin D was more effective for muscle power in younger age groups than in older ones.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In another study, vitamin D was positively associated with isometric flexion and extension average torque at the knee and isokinetic flexion strength at 60°·s −1 and 180°·s −1 ; there was no correlation between vitamin D and knee isokinetic extension strength at 60°·s -1 and 180°·s −1 (12). Previous studies have suggested that vitamin D affected isometric muscle strength (7)(8)(9)(10)(11) and isokinetic muscle strength (7,12,13), but other reports have proposed no effect (12,(14)(15)(16)(17). In this study, improvement was observed in the knee flexor as well as extensor torque and power at 60°·s −1 and 180°·s −1 in all assessed age groups, and the between-group effect sizes for flexion power at 60°·s −1 and extension power at 180°·s −1 after vitamin D supplementation suggested that vitamin D was more effective for muscle power in younger age groups than in older ones.…”
Section: Discussionmentioning
confidence: 93%
“…Although it has been reported that there was no significant effect of vitamin D on muscle power (2,11,14), Bischoof et al (20) stated that there was a significant, positive correlation between muscle power and 25(OH)D only in male participants between 65 and 95 years of age. In another study, vitamin D was positively associated with isometric flexion and extension average torque at the knee and isokinetic flexion strength at 60°·s −1 and 180°·s −1 ; there was no correlation between vitamin D and knee isokinetic extension strength at 60°·s -1 and 180°·s −1 (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations